La materia del sapere. Riflessione ed errore dalla tecno-scienza alla filosofia (e ritorno) - Poccia, Daniele (Bollettino Filosofico, 2023)
What does thinking mean in a world of techno-scientific performativity? And what kind of power can still be attributed to thought? The digital age marks another step in an evolutionary trajectory of technology that moves beyond the concept, requiring a new theoretical grammar, where power relates only to itself. Thinking, as such, implies removing the theological overdetermination of technology and spelling out the modes of knowing that the latter entails. In this view, it is possible to describe the sphere in which thinking and being interact by introducing the concept of error, as an incremental and thus non-absolute becoming. Considering through the lens of error the transfinite nature of reflection, both technological and philosophical, emerges as a matter of the knowledge that, in turn, is also a knowledge of the matter. Keywords: Error, Knowledge, Power, Reflection, Techno-Science